Holistic View of ALK TKI Resistance in ALK-Positive Anaplastic Large Cell Lymphoma - Wang, Yuan; He, Jing; Xu, Manyu; Xue, Qingfeng; Zhu, Cindy; Liu, Juan; Zhang, Yaping; Shi, Wenyu (Frontiers in Oncology, 2022)
Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase expressed at early stages of normal development and in various cancers including ALK-positive anaplastic large cell lymphoma (ALK+ ALCL), in which it is the main therapeutic target. ALK tyrosine kinase inhibitors (ALK TKIs) have greatly improved the prognosis of ALK+ALCL patients, but the emergence of drug resistance is inevitable and limits the applicability of these drugs. Although various mechanisms of resistance have been elucidated, the problem persists and there have been relatively few relevant clinical studies. This review describes research progress on ALK+ ALCL including the application and development of new therapies, especially in relation to drug resistance. We also propose potential treatment strategies based on current knowledge to inform the design of future clinical trials.